The Role of IFS and BRC Standards in Supplier Assessments - Balon, Urszula; Sikora, Milena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Food industry companies have an obligation to ensure the safety of products by implementing the mandatory requirements laid out for GHP, GMP and HACCP systems. Additionally, they can also implement ISO 22000 requirements. However, retailers additionally require of suppliers an IFS and/or BRC certificate. The article presents the requirements of IFS and BRC standards, with particular emphasis on audits as part of the verification of the requirements. Comparisons of requirements of both standards are also described. IFS/BRC standards compliance certified companies reap numerous benefits, including the opportunity to sell their products to markets throughout the world.